Penyegaran Kader Posyandu untuk Meningkatkan Keterampilan Komunikasi dan Informasi mengenai Pemeriksaan Kehamilan - Christina Rony Nayoan; Marni Marni (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2024)
Interventions on posyandu cadres have proven effective in the field of maternal and child health (MCH), primarily associated with infant and newborn mortality. This community service activity aims to improve the knowledge and skills of posyandu cadres to carry out communication, information and education (KIE) for pregnant women related to antenatal care (ANC). The results of the initial assessment in the field conducted by the community service team showed that the problem faced by posyandu cadres in Baadale Village, Rote Ndao Regency was the lack of knowledge and skills to carry out Communication, Information and Education about antenatal care and childbirth preparations that must be carried out to ensure mothers and babies are born healthy and safe. This activity aims to improve the knowledge and skills of Baadale Village posyandu cadres in carrying out Communication, Information and Education regarding Pregnancy examination or Antenatal Care (ANC).Â  The activities have been successfully carried out because 80% of participants' knowledge about ANC has increased. In addition, from the results of demonstrations and simulations, all cadres have improved their skills, as shown by their ability to be able to use health promotion media and interpersonal communication manuals for posyandu cadres.